Choice and experimental substantiation of tests for controlling physical and technical preparedness of hockey players - Kostiukevych, V.; Lazarenko, N.; Vozniuk, T.; Shchepotina, N.; Shynkaruk, O.; Voronova, V.; Borysova, O.; Didyk, T.; Perepelytsia, O.; Hudyma, S.; Bezmylov, N. (Journal of Physical Education and Sport, 2020)
Introduction. In practice of the preparation of athletes in sports games, tests for determining various levels of preparedness are widely used. Tests proposed for field hockey by Nevmianov, Osintsev (1989) were used many times to determine the level of general and special technical preparedness of high qualification athletes in this sport. However, purposeful use of tests to determine the level of physical, functional and technical preparedness of field hockey players must be conditioned upon the determination of their validity (reliability and informativeness) which constitutes subject of this research. Research purpose -to experimentally substantiate the reliability and informativeness of tests for determining the level of physical and technical preparedness of high qualification athletes in field hockey. Material and methods: analysis and summary of special literature and data from the Internet, pedagogical monitoring, questionnaire survey, methods of mathematical statistics. Research was conducted during the competition period of an annual macrocycle. Testing was performed in the intergame microcycles. Tests were conducted under the same conditions, at the same time, by the same experimenters. Before starting the tests, athletes were asked to have a rest for at least 24 hours. Before testing, medical health status questionnaires of athletes were studied. If the average value of health was below 4 points (on a five-point scale), then tests were not conducted. Participants: field hockey players of high qualification, Masters of Sport of Ukraine, students (n=16, age 18-22 years) agreed to participate in this experiment. Each of them was given the same experimental task. Results. Based on the dispersion and correlation analysis, the validity of tests of general physical and special physical preparedness in combination with technique of field hockey players of high qualification was experimentally substantiated. Values of reliability (0,661-0,991) and informativeness coefficients (0,321-0,815) were determined.In order to assess special physical preparedness of athletes in combination with technique with respect to field hockey. Conclusions. The following tests were chosen for controlling general physical preparedness in field hockey players: 30 m run from high start; 60 m run from high start; 180 m Shuttle run test; quintuple jump from the spot; for testing special physical preparedness in combination with technique: long-distance ball shot with a hockey stick; 14,63 m run with ball knockout; dribbling the ball, dribbling around the poles, shot on goal; dribbling the ball, shot on target (performed 6 times); dribbling the ball, dribbling the ball around the pole, shot on goal (performed 5 times).Experimental verification of the reliability (repeatability) shows that all the selected tests for general physical preparedness and special physical preparedness in combination with technique (except for 14,63 meter run with ball knockout) have the acceptable level of reliability. Level of informativeness of the selected tests corresponds to the average and strong correlation relationship.